2022
DOI: 10.3389/ftmal.2022.912723
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Solidification Process of Metal Alloys Under Microgravity Conditions

Abstract: The solidification of metal alloys under low gravity conditions mainly deviates in four physical properties compared with samples solidified on earth. The coarseness of the structure and the solidification temperature increase. The latent heat and the solubility of alloying elements in solids are changed. Experimental results are presented and analyzed in order to find a unified theoretical understanding. The differences in the measured quantities between experiments performed in space and on earth were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Recently, a study on the effect of gravity on the heat of fusion and melting temperature was reported (Fredriksson, 2022). As previously discussed, an increase in the vibration amplitude resulted in the formation of larger clusters because of the decrease in the rotation rate with decreasing gravity.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, a study on the effect of gravity on the heat of fusion and melting temperature was reported (Fredriksson, 2022). As previously discussed, an increase in the vibration amplitude resulted in the formation of larger clusters because of the decrease in the rotation rate with decreasing gravity.…”
Section: Discussionmentioning
confidence: 90%